Prompt and non-prompt J / ψ elliptic flow in Pb+Pb collisions at s NN = 5.02 Tev with the ATLAS detector - Aaboud, M; Aad, G; Abbott, B; Abdinov, O; Abeloos, B; Abhayasinghe, D K; Abidi, S H; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abulaiti, Y; et al. (The European physical journal. C, Particles and fields, 2018)
The elliptic flow of prompt and non-prompt J / ψ was measured in the dimuon decay channel in Pb+Pb collisions at s NN = 5.02 TeV with an integrated luminosity of 0.42 nb - 1 with the ATLAS detector at the LHC. The prompt and non-prompt signals are separated using a two-dimensional simultaneous fit of the invariant mass and pseudo-proper decay time of the dimuon system from the J / ψ decay. The measurement is performed in the kinematic range of dimuon transverse momentum and rapidity 9 < p T < 30 GeV , | y | < 2 , and 0-60% collision centrality. The elliptic flow coefficient, v 2 , is evaluated relative to the event plane and the results are presented as a function of transverse momentum, rapidity and centrality. It is found that prompt and non-prompt J / ψ mesons have non-zero elliptic flow. Prompt J / ψ v 2 decreases as a function of p T , while for non-prompt J / ψ it is, with limited statistical significance, consistent with a flat behaviour over the studied kinematic region. There is no observed dependence on rapidity or centrality.